A Cidade e o Meretrício: trilhas e memórias do mundo da cancela Tianguá-Ceará (1950-2002) - Monteiro, Francisco Gleison da Costa (2004)
This work is the analysis of the speech in the city of Tianguá-Ceará (1950-2002). In the second half of the twentieth century, there is the flow of people and goods that dynamizes the city making Tianguá, following the footsteps of a "metropolis", benefited by geographic centralization and road junctions.[...]